Engagement of CEACAM1 by Helicobacter pylori HopQ Is Important for the Activation of Non-Canonical NF-kappa B in Gastric Epithelial Cells - Taxauer, Karin; Hamway, Youssef; Ralser, Anna; Dietl, Alisa; Mink, Karin; Singer, Bernhard B.; Gerhard, Markus; Mejias-Luque, Raquel; Vieth, Michael (Microorganisms, 2021)
The gastric pathogen Helicobacter pylori infects half of the world's population and is a major risk factor for gastric cancer development. In order to attach to human gastric epithelial cells and inject the oncoprotein CagA into host cells, H. pylori utilizes the outer membrane protein HopQ that binds to the cell surface protein CEACAM, which can be expressed on the gastric mucosa. Once bound, H. pylori activates a number of signaling pathways, including canonical and non-canonical NF-kappa B. We investigated whether HopQ-CEACAM interaction is involved in activating the non-canonical NF-kappa B signaling pathway. Different gastric cancer cells were infected with the H. pylori wild type, or HopQ mutant strains, and the activation of non-canonical NF-kappa B was related to CEACAM expression levels. The correlation between CEACAM levels and the activation of non-canonical NF-kappa B was confirmed in human gastric tissue samples. Taken together, our findings show that the HopQ-CEACAM interaction is important for activation of the non-canonical NF-kappa B pathway in gastric epithelial cells.
CRIS-Team WoS Importer:2021-09-10